IMPROVED RESISTANCE TO TRACTION OF CHISEL-CULTIVATOR WORKING BODIES - M. T. Mansurov; B. U. Toshpolatov; O.N. Toshpolatov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In order to determine the traction resistance of the improved chisel-cultivator working bodies in the direction of increasing the quality of work and reducing the energy consumption, an analytical expression was derived and analyzed, taking into account their working conditions and the arrangement scheme in the frame. Calculations based on the obtained expression showed that the resistance of the improved chisel-cultivator working bodies at a working speed of 6-9 km/h is 8.2-8.6 kN/m, corresponding to its coverage width of one meter.